Sphingosine-1-Phosphate Promotes the Persistence of Activated CD4 T Cells in Inflamed Sites - Jaigirdar, Shafqat Ahrar; Benson, Robert A.; Elmesmari, Aziza; Kurowska-Stolarska, Mariola Stefania; McInnes, Iain B.; Garside, Paul; MacLeod, Megan K. L. (Frontiers in Immunology, 2017)
Inflammation can be protective or pathogenic depending on context and timeframe. Acute inflammation, including the accumulation of CD4 T cells, accompanies protective immune responses to pathogens, but the presence of activated CD4 T cells at sites of inflammation is associated with chronic inflammatory disease. While significant progress has been made in understanding the migration of CD4 T cells into inflamed sites, the signals that lead to their persistence are poorly characterized. Using a murine ear model of acute inflammation and intravital two-photon imaging, we have dissected the signals that mediate CD4 T cell persistence. We report the unexpected finding that the bioactive lipid, sphingosine-1-phosphate (S1P), is both necessary and sufficient for the persistence of activated CD4 T cells at peripheral tissues in acute inflammation. S1P mediated the enhanced motility of CD4 T cells at inflamed tissues but did not affect their migration to the downstream draining lymph node. We found that sphingosine kinase-1, which regulates S1P production is increased at inflamed sites in mice and in patients with the chronic inflammatory disease, rheumatoid arthritis. Together, these data suggest that S1P, or its regulators, may be key targets to promote or disrupt accumulation of CD4 T cells at inflamed tissues.